Determinants of Audit Report Delay: Further Evidence from Saudi Arabia - Abdullah Alhadadi (Journal of Accounting and Management Information Systems (JAMIS), 2024)
Research Question- What are the determinants of audit report delay (ARD) among publicly traded firms in Saudi Arabia? Motivation- The motive to investigate audit report delays (ARD) in the Saudi context is driven by the critical need for timely disclosure of financial information. In emerging markets like Saudi Arabia, where information access is limited and delays are expected, understanding ARD determinants can offer insights into the efficiency of the audit process. Additionally, prior studies on the determinants of ARD have produced mixed and inconclusive results, likely due to the limited scope of their models. By examining both auditor- and client-related factors, this study fills these gaps and explores how governance practices influence audit timeliness, ultimately enhancing financial reporting quality. Idea- This study adopts a more comprehensive model to investigate potential determinants of ARD, encompassing a broad spectrum of auditor-related and client-related variables. Data- This study is based on a sample of non-financial listed firms, encompassing 1,191 firm-year observations during the 2006–2021 period. Financial data are downloaded from the S&P Capital IQ database, while corporate governance data are hand-collected from the firms' annual reports. Tools- The study uses multiple OLS regressions to predict the impact of the auditor and client attributes on ARD. Findings- The results revealed that auditor change, tenure, audit committee size, audit committee independence, board size, and board independence are associated with shorter ARD. Conversely, auditor size, frequency of audit committee meetings, and frequency of board meetings are associated with prolonged ARD. Contribution- The present study makes a significant contribution to the literature on audit reporting delay, audit efficiency, timeliness of reporting, and corporate governance. It offers a clearer understanding of the multifaceted nature of ARD, which is crucial for audit firms and regulatory bodies. The insights gained from this research can help develop strategies to reduce ARD, ultimately enhancing audit efficiency and reducing information asymmetries in capital markets, thus fostering more transparent financial reporting and better-informed investors.
Keywords: M41; M42; 650; Audit Report Delay (ARD); Corporate Governance; Financial Reporting; Saudi Arabia